Analisis Kinerja Insinerator Menggunakan Sistem Monitoring Suhu dan Gas Buang - Gunawan, Gunawan; Supardin, Supardin; Idwar, Idwar; Rahmawati, Rahmawati; Mardiyanto, Arief (Politeknik Negeri Lhokseumawe, 2025)
Waste management is a challenge because landfills are almost full. Incineration is a vital solution in waste management because it can significantly reduce waste volume and eliminate hazardous substances through a high-temperature combustion process of at least 600 °C, thereby helping to reduce waste accumulation in landfills and its impact on the environment. Monitoring temperature and exhaust gas is essential to ensure combustion efficiency and maintain emissions within safe limits. This study aims to design and implement an accurate real-time monitoring system to support incinerator management to be more efficient and environmentally friendly. Temperature monitoring uses a thermocouple sensor and the MAX6675 module, exhaust gas emissions use MQ7 and MQ135 sensors to detect CO and CO2. The thermocouple sensor used has an accuracy level of 99.23%, while exhaust gas monitoring uses an MQ-135 sensor to measure CO2 with an accuracy of 98.93 % and an MQ-7 sensor for CO with an accuracy of 92.14 %. No-load incinerator temperature testing showed a peak temperature of 323 °C, which then decreased due to fuel depletion. Testing with waste load showed the temperature increased more slowly but reached a higher peak of 616 °C. During the combustion process, CO content increased to 150 ppm during incomplete combustion, while CO2 peaked at 6,000 ppm and then decreased as complete combustion progressed. Future expectations require improvements in air flow regulation and the application of a scrubbing system to optimize combustion and reduce emissions.